Pengaruh Model Pembelajaran Learning Cycle 5E terhadap Kemampuan Pemecahan Masalah Matematika Ditinjau dari Adversity Quotient Siswa - Abdul Ma'arif; Syaiful Syaiful; Muhammad Haris Effendi Hasibuan (Universitas Syiah Kuala, 2020)
Problem-solving skill is required by students and a target in studying mathematics. However, the problem-solving skill of Indonesian students are lacking. One effort that can be done is applying the Model of Learning Cycle 5E. This research discussed the influence of the implementation of the learning cycle model on mathematics problem-solving skill viewed from students adversity quotient. This research used a quantitive approach, quasi-experimental study. The subjects were the 8th Grade students of SMP IT Ash-Shiddiiqi Jambi, consisting of two experiment classes and one control class. The instruments were post-test and adversity quotient questionnaire modified by Stoltz and had been validated by experts. Data analysis was conducted by Two-Way ANOVA. The results showed that there was no interaction between the learning cycle 5E model and mathematics problem-solving skill. This finding indicates that the model of learning cycle 5E affects problem-solving skills and can be applied to students with all types of adversity quotient.